RNA interference: trends in small regulatory rnas and gene silencing - RICHA ANAND, (International Journal of Pharma and Bio Sciences, 2017)
RNAi pathway is a biologically conserved phenomenon which regulates the expression of genes through transcriptional or post-transcriptional gene silencing mechanism. The pathway involves the network of different proteins to degrade the target mRNA and triggered by small regulatory RNAs. These small regulatory RNAs are generated via action of dicer enzyme on long double-stranded RNA or hairpin RNA. Herein, we have explained the significant classes of small RNAs, their functions, and mechanism of RNAi as well. Along with, we have highlighted the recent findings in RNAi, glimpse of available small RNAs repositories, and softwares/tools for their efficient designing.